Supplementary data - Supplemental material for α-Glucosidase Inhibitory Activity of Resin From Sakhalin fir Tree ( Abies sachalinensis ) and its Bioactive Compounds ... - Nakagawa, Toshinori; Ashour, Ahmed; Yhiya Amen; Koba, Yurie; Ohnuki, Koichiro; Kuniyoshi Shimizu (SAGE Journals, 2019)
Supplemental material, Supplementary data, for α-Glucosidase Inhibitory Activity of Resin From Sakhalin fir Tree ( Abies sachalinensis ) and its Bioactive Compounds by Toshinori Nakagawa, Ahmed Ashour, Yhiya Amen, Yurie Koba, Koichiro Ohnuki, and Kuniyoshi Shimizu in Natural Product Communications ...